2018
DOI: 10.1111/josh.12646
|View full text |Cite
|
Sign up to set email alerts
|

School Professionals' Knowledge and Beliefs About Youth With Chronic Illness

Abstract: More training and support is needed for school professionals in their work with students with chronic illness. Assessments may be useful at a local level to help schools develop better policies and plans for educating youth with chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
(42 reference statements)
0
19
0
2
Order By: Relevance
“…Both teacher and other school staff note the lack of resources and training, especially on school policy and staff responsibilities in chronic condition management, that contribute to frustration. Non-instructional and afterschool staff experience similar challenges as classroom teachers (Berger et al, 2018). Millions of students attend afterschool programs such as sports, clubs, and academic enrichment activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both teacher and other school staff note the lack of resources and training, especially on school policy and staff responsibilities in chronic condition management, that contribute to frustration. Non-instructional and afterschool staff experience similar challenges as classroom teachers (Berger et al, 2018). Millions of students attend afterschool programs such as sports, clubs, and academic enrichment activities.…”
Section: Introductionmentioning
confidence: 99%
“…Communication between school health services and afterschool staff about student chronic condition management is imperative in these settings (CDC, 2019). However, when a variety of school staff were surveyed, most were not aware of the barriers to optimal participation faced by students with chronic health conditions; they lacked knowledge of the association between health conditions and academic and social outcomes, and they perceived little support for addressing students with less common chronic conditions (Berger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Second, school nurses reported that a team‐based approach, including effective communication and collaboration with parents, school staff, and health care providers, could facilitate school health care (Allen et al, 2012; Garwick et al, 2015; March et al, 2020; Seki et al, 2017; Thorstensson et al, 2016; Williams et al, 2019). They expressed a greater need for collaboration between schools, families, and health care providers than other school professionals (Berger et al, 2018). They further perceived the need for early, open, and clear communication about diagnoses from the health care team (Terry & Trott, 2019), and for meetings for stakeholders (Williams et al, 2019) as facilitators.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these limitations, school nurses are more likely than teachers or counselors to recognize challenges and the need for support and collaboration (Berger, Valenzuela, Tsikis, & Fletcher, 2018). Barriers to asthma management faced by school nurses (Hanley Nadeau & Toronto, 2016) and school nurses' interventions and outcomes (Best et al, 2018) have been previously reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The Children and Families Act36 outlines the duty of schools’ to ensure pupils with medical conditions are supported 37. However, the literature indicates a gap in the knowledge of schools about chronic diseases, such as IBD 38 39. This illustrates the vital role of effective liaison between health and education, with the provision of training/support, further highlighted by many responses indicating nurse specialists educating teachers could result in improved attendance (figure 1).…”
Section: Discussionmentioning
confidence: 99%